Business Model Canvas (BMC) sebagai Strategi Penguatan Kompetensi UMKM Makanan Ringan di Kabupaten Kebumen, Jawa Tengah - Nur Wijayanti; Hety Handayani Hidayat (JURNAL AGROINDUSTRI HALAL, 2020)
Micro, Small and Medium Enterprises (SME) Snack food in Kebumen Regency is a startup (starter entrepreneurial) that produces snacks, but have a good business model not yet. This study aims to determine the business strategy that is carried out, analyze the strengths and weaknesses of business processes, and provide recommendations for improving SME competencies using the canvas business model. The method used in this research is descriptive qualitative method. The results of the study illustrate that SME have a value proposition that is snacks in the form of healthy snacks and has local branding. To create value propositions, SME partners such as suppliers of raw materials and consumers, become the main SME resources to run production and distribution, which also requires costs. SME income is only through product sales. Recommendations from this research are to participate as sponsors in various community and humanitarian activities, cooperation and fostering of farmers, resellers, packaging improvements, halal product certification, and product development. Keywords: Business Model Canvas, Snack SME, Kebumen